THE RISK FACTORS FOR DRUG INDUCED HEPATITIS IN PULMONARY TUBERCULOSIS PATIENTS IN DR. SOETOMO HOSPITAL - Soedarsono, Soedarsono; Mandayani, Sari; Prayuni, Kinasih; Yuliwulandari, Rika (Indonesian Journal of Tropical and Infectious Disease, 2018)
Tuberculosis (TB) is still a major public health problem in Indonesia. Anti-tuberculosis drug-induced hepatotoxicity (DIH) is common side effect leading to changes in treatment regimens, and the less effective second-line treatments. Several risk factors such as age, sex, body mass index (BMI) and acetylization status for hepatotoxicity were suggested in previous studies but in the fact, those are often not related to DIH incidence after receiving standard TB treatment regimen. The aim of this study was to asses the role of risk factors in the DIH incidence in pulmonary TB patients receiving standard TB treatment regimen in Dr. Soetomo Hospital, Surabaya. Study design was analytic observational with case control. The subjects were 30 TB DIH patients and 31 TB non-DIH patients receiving standard national TB program therapy. DIH severity was divided based on International DIH Expert Working Group. Demographic data and BMI status were taken from medical records. The age classification are â‰¥35 years old and <35 years old as one of the risk factors studied. DNA sequencing was used to assess single-nucleotide polymorphisms in NAT2 coding region to evaluate acetylator status from blood samples. The risk factors were evaluated using chi-square test and Mantel-Haenszel test. Significant association between low BMI and DIH in general was identified (OR=3.017; 95% CI=1.029-8.845) and more significant association between low BMI and moderate DIH (OR=15.833; 95% CI=1.792-139.922). Age, sex, and acetylization status has no significant correlation with DIH incidence in general. Significant association between slow acetylator phenotype and incidence of moderate DIH was identified (OR=7.125; 95% CI= 1.309-38.711). In conclusion, some risk factors were correlated to DIH incidence in pulmonary TB patientsreceiving standart TB treatment regimen.